A Review on Collaborative Robot Assembly Line Balancing Problems - Kheirabadi, M.; Keivanpour, S.; Chinniah, Y.; Frayret, J.M. (IFAC-PapersOnLine, 2022)
Assembly line balancing problems have been the subject of numerous studies for decades. The recent advantages of technologies in the Industry 4.0 era and integrating collaborative robots into the assembly systems have created task allocation, workload balance, and scheduling challenges. This paper provides a brief literature review on the existing collaborative assembly line balancing problems comparing their main characteristics and suggests some research directions for future studies.